Dé/faire les corporéités queers en contexte néolibéral - Jordan Fraser Emery (Communication)
This study examines the dynamics of queer expression in a neoliberal environment with Guma Joana and Amem Yhra, two cross-dressing artists from São Paulo. It explores how their Instagram profiles and participation in the Casa de Criadores event act as intermediary platforms between their informal creativity and the formal structures of creativity they aspire to integrate. Although these platforms allow visibility and promise social recognition, they also raise the question of how the resources from their lived experience are valued and exploited, which can perpetuate forms of social dominance. The study is part of a reflection on the paradoxes of capitalist individualization, using visual semiotics in dialogue with philosophy and aesthetics.